2005
DOI: 10.1002/jctb.1302
|View full text |Cite
|
Sign up to set email alerts
|

Production of ellagic acid from degradation of valonea tannins by Aspergillus niger and Candida utilis

Abstract: Two fungal strains, effective in converting valonea (Quercus aegilops) tannins into ellagic acid (EA), were isolated from soil contaminated by valonea tannins, and were tentatively identified as Aspergillus niger and Candida utilis. Properties of EA accumulation by the two isolates from valonea tannins' fermentation were studied. Both the strains preferred sucrose to glucose as the additional carbon and energy source. The most suitable concentrations of valonea tannins in fermentation media for EA accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 15 publications
0
24
0
1
Order By: Relevance
“…DiVerences in time of tannin acyl hydrolase production and EA accumulation can be explained by the fact that gallotannins are more biodegradable than ellagitannins as described recently by Mingshu et al [21] and Aguilar et al [3]. The EA production was higher than the values reported by other [14,[27][28][29]; however, the optimization of the process to produce EA is necessary. In addition, EA accumulation was not associated with tannin acyl hydrolase activity and it partially supported the hypothesis proposed by Aguilar et al [3] about the diVerence between the tannin acyl hydrolase (gallo-tannase) and the unknown "ellagi-tannase."…”
Section: Resultsmentioning
confidence: 42%
See 1 more Smart Citation
“…DiVerences in time of tannin acyl hydrolase production and EA accumulation can be explained by the fact that gallotannins are more biodegradable than ellagitannins as described recently by Mingshu et al [21] and Aguilar et al [3]. The EA production was higher than the values reported by other [14,[27][28][29]; however, the optimization of the process to produce EA is necessary. In addition, EA accumulation was not associated with tannin acyl hydrolase activity and it partially supported the hypothesis proposed by Aguilar et al [3] about the diVerence between the tannin acyl hydrolase (gallo-tannase) and the unknown "ellagi-tannase."…”
Section: Resultsmentioning
confidence: 42%
“…Recent studies on EA production are very scarce but they are very promising and they have reported the use of cranberry pomace fermented in a solid state culture using Lentinus edodes [28,29]; authors attributed the catalysis to the enzyme -glucosidase, Also, valonea tannins have been used to produce EA in axenic culture of Aspergillus niger SHL [14] or in co-culture of Candida utilis and A. niger [27]. However, low yields and long times are involved in the bioprocess.…”
Section: Introductionmentioning
confidence: 99%
“…A. niger and Candida utilis isolated from valonea tannin fermentation preferred sucrose to glucose as the additional carbon and energy source. These strains were able to degrade 20 g dm −3 valonea tannins completely with an ellagic yield of 14.3% in 9 days (Shi et al 2005). It has been found that Escherichia coli degrades phenol compound and also helps in simultaneous reduction of Cr(VI) to Cr(III) (Shen et al 1995).…”
Section: Biodegradation Of Tannins Dyes and Mixturesmentioning
confidence: 96%
“…However, about the enzyme(s) involved in the process of ellagitannins biodegradation, the information is scarce and confuse. Shi et al (2005) hypothesized the role of typical tannase (tannin acyl hydrolase, TAH) and polyphenol oxidase in this biochemical event. Some reports of tannin biodegradation have been published (Bath et al 1998;Aguilar et al 2007), and the role of a nontypical tannase (ellagitannase) has been seriously considered and partially demonstrated in the studies carried out by Huang et al (2007a, b, c, d).…”
Section: Introductionmentioning
confidence: 99%
“…1). To obtain EA from plants, some studies on hydrolyzing ellagitannins with acid or base have been reported (Daniel et al 1991;Shi et al 2005). Due to variation in plant sources, the differences of ellagitannins structure, and the difficulty of purification, these chemical methods often lead to low yields of EA and considerable impurities.…”
Section: Introductionmentioning
confidence: 99%